2010
DOI: 10.1021/jm100571n
|View full text |Cite
|
Sign up to set email alerts
|

4-(Pyrazol-4-yl)-pyrimidines as Selective Inhibitors of Cyclin-Dependent Kinase 4/6

Abstract: Identification and structure-guided optimization of a series of 4-(pyrazol-4-yl)-pyrimidines as selective CDK4/6 inhibitors is reported herein. Several potency and selectivity determinants were established based on the X-ray crystallographic analysis of representative compounds bound to monomeric CDK6. Significant selectivity for CDK4/6 over CDK1 and CDK2 was demonstrated with several compounds in both enzymatic and cellular assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 56 publications
(37 reference statements)
1
45
0
Order By: Relevance
“…Moreover, phosphorylation of Thr172 in the T-loop does not result in the activation of the enzyme bound to cyclin D1. Furthermore, there are several 3.10 1JOW CDK6 -Vcyclin -9-cyclopentyl-N-(5-piperazin-1-ylpyridin-2-yl)pyrido [4,5]pyrrolo[1,2-d]pyrimidin-2-amine 109 2.90 4TTH CDK6 -Vcyclin -Aminopurvalanol 114 2.80 2F2C CDK6 -Vcyclin -Fisetin 117 2.90 1XO2 CDK6 -Vcyclin -PD0332991 114 3.00 2EUF CDK6 -Kcyclin -p18 INK4c 118 2 111 2.70 4EZ5 CDK6 -1H-benzimidazol-2-yl(1H-pyrrol-2-yl)methanone 111 2.31 4AUA CDK6 -4-[3-(1-methylethyl)-1H-pyrazol-4-yl]-N-(1-methylpiperidin-4-yl)pyrimidin-2-amine 119 2.60 3NUP CDK6 -4-[5-chloro-3-(1-methylethyl)-1H-pyrazol-4-yl]-N-(5-piperazin-1-ylpyridin-2-yl)pyrimidin-2-amine 119 2.70 3NUX CDK6 -p16 INK4a 83 3.40 1BI7 CDK6 -p19 INK4d 74,83 1.90 1BLX 2.80 1BI8 lines of evidence showing that CDK4 might not even be phosphorylated by CAK. 77,78 The INK4 family of CDK inhibitors (CDKIs) which include p16 INK4a , p15 INK4b , p18 INK4c , and p19 INK4d are specific to CDK4 and CDK6.…”
Section: Structural Features and Regulationmentioning
confidence: 99%
“…Moreover, phosphorylation of Thr172 in the T-loop does not result in the activation of the enzyme bound to cyclin D1. Furthermore, there are several 3.10 1JOW CDK6 -Vcyclin -9-cyclopentyl-N-(5-piperazin-1-ylpyridin-2-yl)pyrido [4,5]pyrrolo[1,2-d]pyrimidin-2-amine 109 2.90 4TTH CDK6 -Vcyclin -Aminopurvalanol 114 2.80 2F2C CDK6 -Vcyclin -Fisetin 117 2.90 1XO2 CDK6 -Vcyclin -PD0332991 114 3.00 2EUF CDK6 -Kcyclin -p18 INK4c 118 2 111 2.70 4EZ5 CDK6 -1H-benzimidazol-2-yl(1H-pyrrol-2-yl)methanone 111 2.31 4AUA CDK6 -4-[3-(1-methylethyl)-1H-pyrazol-4-yl]-N-(1-methylpiperidin-4-yl)pyrimidin-2-amine 119 2.60 3NUP CDK6 -4-[5-chloro-3-(1-methylethyl)-1H-pyrazol-4-yl]-N-(5-piperazin-1-ylpyridin-2-yl)pyrimidin-2-amine 119 2.70 3NUX CDK6 -p16 INK4a 83 3.40 1BI7 CDK6 -p19 INK4d 74,83 1.90 1BLX 2.80 1BI8 lines of evidence showing that CDK4 might not even be phosphorylated by CAK. 77,78 The INK4 family of CDK inhibitors (CDKIs) which include p16 INK4a , p15 INK4b , p18 INK4c , and p19 INK4d are specific to CDK4 and CDK6.…”
Section: Structural Features and Regulationmentioning
confidence: 99%
“…Previously reported structural studies with selective inhibitors bound to CDK6 propose an aromatic sp2 nitrogen in proximity to His100 (His92 in CDK4) as an important determinant for selectivity over other kinases. 16,18,22 Analysis of the structural information in Figure 1 suggested that replacing the benzimidazole with 7-azabenzimidazole would provide an opportunity to test this hypothesis. Indeed, the 7-azabenzimidazole analogue 3 was the first compound to exhibit greater than 10-fold selectivity for CDKs 4 and 6 over CDKs 1 and 2.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…These results indicated a comparable or improved selectivity profile relative to currently published CDK4/6 selective inhibitors. 16,18 A critical aim of this project was to generate compounds with a high degree of selectivity for CDK4/6 over CDK1/2. During the optimization process, certain modifications were made to the molecule, not solely to increase CDK4/6 potency but to drive the high selectivity over CDK1/2.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…It indicates that selective CDK4/6 inhibitors potentially have a larger therapeutic window compared with pan-CDK inhibitors [5]. Selectivity of the CDK-inhibitors isimportant for their anticancer pharmacological activity [3].…”
Section: Introductionmentioning
confidence: 99%
“…The substituents at the parent compound which replaced are chlorine (R 2 ) and isopropyl (R 1 ) at the pyrazole ring. Substitution at R 1 position affects its hydrophobic interaction toward CDKs and substitution at R 2 can affect its CDK4 inhibition activity [5].…”
Section: Introductionmentioning
confidence: 99%